İsmail Hakkı Bursevi’nin Şerhu’l-kebair adlı eserinin tanıtımı ve tahlili - Güler, İbrahim Halil (My University, 2005)
İsmail Hakkı Bursevî'nin Şerhu'l-Kebâir Adlı Eserinin Tanıtımı Ve Tahlili adıyla hazırlanan bu tez üç bölümden oluşmaktadır. İlk bölümde, İsmail Hakkı ve incelediğimiz eseri Şerhu'l-Kebâir hakkında bilgi verilmiştir. İkinci bölümde, eser müellif nüshası baz alınarak latinize edilmiş, sonra da üç farklı nüshadan karşılaştırıp, farklılıkları dipnot halinde gösterilmiştir. Üçüncü bölümde ise eserde geçen ve daha çok tasavvufun alanına giren, ahlak ve mâneviyâtla ilgili büyük günahlar, eserden hareketle, tasavvuf klasiklerimizden de faydalanılarak, konu bütünlüğü içinde tahlil edilmiştir. Name: İbrahim Halil Surname: GÜLER Consultant: Prof. Dr. Hasan Kamil YILMAZ Thesis named: Analysis of the Book of Şerhu'l-Kebair written by İsmail Hakkı Bursevi. Mother Science Branch: Foundation of İslamic Sciences. Science Branch: Sufism. Key word: Big sins

The thesis which is named as Introducing, and analysis of the Book of Şerhu'l-Kebair written by İsmail Hakkı Bursevi, contains three chapters. In the first chapter, it is given an information about the book Şerhu'l-Kebâir which was analised in the thesis and the author İsmail Hakkı. In the second chapter, book it was latinized, taking the authors copy as a basis. Then three different copies were compared with the authors copy, and the differences between them, were showed in the footnotes. In the third chapter, the big sins mentioned in the book and especially related with the sufism, are analised, by utilising with the sufic classics, in the integrity of the subject.
Keywords: Akâid ve Kelâm; Büyük Günahlar; Din; İslam Dini; İsmail Hakkı Bursevi; Şerhu’l-kebair; Tasavvuf